2021
DOI: 10.1016/j.redox.2021.102201
|View full text |Cite
|
Sign up to set email alerts
|

LRPPRC regulates redox homeostasis via the circANKHD1/FOXM1 axis to enhance bladder urothelial carcinoma tumorigenesis

Abstract: Reactive oxygen species (ROS) which are continuously generated mainly by mitochondria, have been proved to play an important role in the stress signaling of cancer cells. Moreover, pentatricopeptide repeat (PPR) proteins have been suggested to take part in mitochondrial metabolism. However, the mechanisms integrating the actions of these distinct networks in urothelial carcinoma of the bladder (UCB) pathogenesis are elusive. In this study, we found that leucine rich pentatricopeptide repeat containing (LRPPRC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…Leucine-rich pentatricopeptide repeat motif-containing protein (LRPPRC) is a multifunctional protein localized to the mitochondria, endoplasmic reticulum, outer and inner nuclear membranes, nucleoplasm, and cytoskeleton [ 40 , 41 ]. Besides being a prognostic factor, LRPPRC has recently been demonstrated to enhance tumorigenesis in bladder cancer [ 42 ].…”
Section: Roles Of Mitochondria In Ucmentioning
confidence: 99%
“…Leucine-rich pentatricopeptide repeat motif-containing protein (LRPPRC) is a multifunctional protein localized to the mitochondria, endoplasmic reticulum, outer and inner nuclear membranes, nucleoplasm, and cytoskeleton [ 40 , 41 ]. Besides being a prognostic factor, LRPPRC has recently been demonstrated to enhance tumorigenesis in bladder cancer [ 42 ].…”
Section: Roles Of Mitochondria In Ucmentioning
confidence: 99%
“…Many studies have demonstrated that circRNAs can act as sponges for microRNAs (miRNAs) or bind to proteins, and altered circRNA levels can lead to aberrant expression of gene products 3 . Importantly, an increasing number of studies have shown that circRNAs are widely expressed in mammals and are expressed to varying degrees in various cancers, such as esophageal squamous cell carcinoma, urothelial carcinoma, and colorectal cancer [4][5][6] . In addition, many circRNAs have been reported to participate in the development of HCC, regulating cell proliferation, tumor metastasis, and glycolysis [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Pentatricopeptide repeat (PPR) proteins are a large class of RNA-binding proteins characterized by a typical thirty-five residue repeat motif [ 13 ]. Only seven PPR proteins are found in human beings, all of which are located in mitochondria and involved in various cell procedures, notably in RNA supersession [ 14 , 15 ]. The discovery of essential role of PPR proteins in mitochondria gene expression and energy metabolism underscores its biological importance [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only seven PPR proteins are found in human beings, all of which are located in mitochondria and involved in various cell procedures, notably in RNA supersession [ 14 , 15 ]. The discovery of essential role of PPR proteins in mitochondria gene expression and energy metabolism underscores its biological importance [ 15 ]. For example, mitochondrial RNA polymerase regulates the transcription of mitochondrial mRNA (mt-mRNA) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation